2005
DOI: 10.22621/cfn.v119i2.119
|View full text |Cite
|
Sign up to set email alerts
|

Passage Through a Small Drainage Culvert by Mule Deer, <em>Odocoilus hemionus</em>, and Other Mammals

Abstract: Cameras with infra-red triggers were used to monitor the passage of wildlife through underground passages that ran under a major highway and railway. Several species of mammals were detected traveling through the passages; of particular interest was the movement of Mule Deer (Odocoileus hemionus) through a relatively small culvert that would not have been predicted to see usage by these animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…mule deer Odocoileus hemionus) or large carnivorous mammals (e.g. black bear Ursus americanus, bobcat Lynx rufus) (Clevenger and Waltho 2000, Krawchuk et al 2005, Marangelo 2019. However, drainage culverts cannot replace conventional wildlife passages for mammals, mainly because the highwater levels and the use of polyethylene as construction material decrease the number of successful passages.…”
Section: Discussionmentioning
confidence: 99%
“…mule deer Odocoileus hemionus) or large carnivorous mammals (e.g. black bear Ursus americanus, bobcat Lynx rufus) (Clevenger and Waltho 2000, Krawchuk et al 2005, Marangelo 2019. However, drainage culverts cannot replace conventional wildlife passages for mammals, mainly because the highwater levels and the use of polyethylene as construction material decrease the number of successful passages.…”
Section: Discussionmentioning
confidence: 99%
“…Livestock underpasses for cattle tend to be box culverts. Dimensions for cattle have been reported as 23 ft (7 m) wide and 16.4 ft (5 m) high (Krawchuk et al 2005) and 26.2 ft (8 m) wide and 9.8 ft (3 m) high (Huijser et al 2016). Two underpasses for feral horses were constructed along the "USA Parkway" between Clark and Silver Springs Nevada (Xu & Tian 2019).…”
Section: Underpass or Overpass Structuresmentioning
confidence: 99%
“…A variety of techniques are used to assess wildlife passageway effectiveness (Abson & Lawrence 2003). A sampling of passageway studies revealed that the most prevalent techniques used are remote camera sensing and track beds (Krawchuk et al 2005, Clevenger & Waltho 2005, Gagnon et al 2007, Olson & Widen 2008, McCollister & Van Menen 2010, Allen 2011. In many studies, cameras were used in conjunction with track beds to verify crossing occurrences; however, these techniques primarily provided information only on the use of structures by wildlife.…”
Section: Conceptual Modelmentioning
confidence: 99%